Surface Kondo effect and non-trivial metallic state of the Kondo insulator YbB12 - Kenta Hagiwara (Nature Portfolio, 2016)
Topological state in Kondo insulators has been provoked in SmB6, but the origin of surface states and topological order remain elusive. Here, Hagiwara et al. report temperature dependent reconstruction of a metallic surface state on the (001) surface of YbB12driven by Kondo effect and discuss its origin from topology.